A Proposal for observing Conceived Ladies having High Risk of Premature Delivery using WHSN - Rani Chintala, Radhika; Rao M R, Narasinga; Venkateswarlu, Somu (International Journal of Engineering and Technology, 2018)
Premature delivery of baby leads to death of babies below the age of 5 years. Even if they survive, they have to leave with a permanent disability like loss of vision, reduced learning abilities and hearing problems. Over the past years researchers have noticed that, observing uterine contractions can help in assessing the advancement of pregnancy and health of baby. It also decides whether pregnant lady is in the process of giving birth and thus accordingly reduce the impacts of premature delivery. This paper proposes a simple, secure, comfortable and cheaper system to screen pregnant ladies who are vulnerable to premature delivery. This system comprises of a wireless Human Sensor Network (HSN) for non-obtrusively observing the uterine contractions and if it is observed that readings are outer the normal limits, then a warning alert is send via a smart device. This paper also proposed a proof-of-idea model and tried it for testing the performance, power utilization and quality of the system.Â Â